Measuring empowerment across the value chain: The evolution of the project-level Women’s Empowerment Index for Market Inclusion (pro-WEAI+MI) - Malapit, Hazel J.; Heckert, Jessica; Adegbola, Patrice Ygué; Crinot, Geraud Fabrice; Eissler, Sarah; Faas, Simone; Gantoli, Geoffroy; Kalagho, Kenan; Martinez, Elena M.; Meinzen-Dick, Ruth S.; Mswero, Grace; Myers, Emily; et al. (International Food Policy Research Institute, 2023)
Many development agencies design and implement interventions that aim to reach, benefit, and empower rural women across the value chain in activities ranging from production, to processing, to marketing. Determining whether and how such interventions empower women, as well as the constraints faced by different value chain actors, requires quantitative and qualitative tools. We describe how we adapted the project-level Women’s Empowerment in Agricultural Index (pro-WEAI), a mixed-methods tool for studying empowerment in development projects, to include aspects of agency relevant for multiple types of value chain actors. The resulting pro-WEAI for market inclusion (pro-WEAI+MI) includes quantitative and qualitative instruments developed over the course of four studies. Studies in the Philippines (2017), Bangladesh (2017), and Malawi (2019) were intended to diagnose areas of disempowerment to inform programming, whereas the Benin (2019) study was an impact assessment of an agricultural training program. The pro-WEAI+MI includes all indicators included in pro-WEAI, plus a dashboard of complementary indicators and recommended qualitative instruments. These tools investigate the empowerment of women in different value chains and nodes and identify barriers to market access and inclusion that may restrict empowerment for different value chain actors. Our findings highlight three lessons. First, the sampling strategy needs to be designed to capture the key actors in a value chain. Second, the market inclusion indicators cannot stand alone; they must be interpreted alongside the core pro-WEAI indicators. Third, not all market inclusion indicators will be relevant for all value chains and contexts. Users should research the experiences of women and men in the target value chains in the context of the programto select priority market inclusion indicators.